Science in The View of Islamic History (The Development of Science During The Early Islamic Period and The Islamic Golden Age) - Sandrina Ramadhani; Sri Juwita; Muhammad Sirozi (FKIP - Universitas Riau, 2026)
This study examines the development of knowledge in the historical perspective of Islam, focusing on the early Islamic period up to the Golden Age of the Abbasid Dynasty. Using a library research method with a qualitative-descriptive approach, the study traces the intellectual progression sparked by the first revelation, “Iqra’,” which served as the foundation for the rise of Islamic scholarship. During the Prophet Muhammad’s era, intellectual growth emphasized moral reform, memorization of the Qur’an, the writing of revelations, and the establishment of Darul Arqam as an educational center. Under the Khulafaur Rasyidin, knowledge advanced through the codification of the Qur’an, the development of ijtihad, the formation of Arabic grammar, and administrative reforms. The Umayyad Dynasty strengthened Islamic scholarship by institutionalizing Arabic as the state language, establishing learning centers, expanding religious sciences, and initiating translation efforts. The peak occurred under the Abbasids through the establishment of the Bayt al-Hikmah, systematic book-compilation methods, and extensive translation movements, producing prominent scholars in mathematics, medicine, philosophy, and religious sciences. This study concludes that the development of knowledge in Islam progressed systematically and significantly shaped global civilization.